The EBRAINS Hodgkin-Huxley Neuron Builder: An online resource for building data-driven neuron models - Bologna, Luca Leonardo; Smiriglia, Roberto; Lupascu, Carmen Alina; Appukuttan, Shailesh; Davison, Andrew P.; Ivaska, Genrich; Courcol, Jean-Denis; Migliore, Michele (Frontiers in Neuroinformatics, 2022)
In the last decades, brain modeling has been established as a fundamental tool for understanding neural mechanisms and information processing in individual cells and circuits at different scales of observation. Building data-driven brain models requires the availability of experimental data and analysis tools as well as neural simulation environments and, often, large scale computing facilities. All these components are rarely found in a comprehensive framework and usually require ad hoc programming. To address this, we developed the EBRAINS Hodgkin-Huxley Neuron Builder, a web resource for building single cell neural models via the extraction of activity features from electrophysiological traces, the optimization of the model parameters via a genetic algorithm executed on high performance computing facilities and the simulation of the optimized model in an interactive framework. Thanks to its inherent characteristics, the Hodgkin-Huxley Neuron Builder facilitates the data-driven model building workflow and its reproducibility, hence fostering a collaborative approach